Low-cost high-resolution distributed optical fiber system for spectrophotometric analysis of liquid samples: Application to detection of azo dyes - Genni Testa; Gianluca Persichetti; Romeo Bernini (Sensors and Actuators Reports, 2024)
A distributed optical fiber system for spectrophotometric analysis of liquid samples based on light diffusing fiber (LDF) is presented. The sensor is based on a high-density white light emitting diode (LED) strip, which is side coupled to a glass based light-diffusing fiber (LDF) that acts as distributed optical receiver. The light emitted from a single LED propagates through the sample medium, is collected by the LDF and is then detected at the end of the fiber by a mini spectrometer. By sequentially turning on one LED at a time, the system permits the spectrophotometric analysis of the sample medium along the entire fiber length. This approach is capable of a continuous monitoring of absorbance spatial profile of liquid sample in the whole visible spectrum with a single low-cost spectrometer. The experimental results confirm the possibility of distributed measurements with a spatial resolution of about 12 mm over 1 m of measurement range. The approach has been successfully employed to the distributed detection and localization of azo dyes in water with a limit of detection lower than 1 ppm.